Dynamics through three-inlets of t-shaped ducts: Significance of inlet velocity on transient air and water experiencing cold fronts subject to turbulence - Wang, Fuzhang; Animasaun, I.L.; Al-Mdallal, Qasem M.; Saranya, S.; Muhammad, Taseer (International communications in heat and mass transfer, 2023)
Efficiency, management, and control of air and water dynamics subject to cold fronts within ducts are among the problems that occur in the water industry and during the production of gases. This article presents the dynamics of unsteady air and water through a three-inlet t-shaped duct, emphasizing the problem of cold fronts. Attempts were made to remark on the nature of these fluids a few distances after the mixture (70 mm), before turning of the duct, and after turning the duct. The realizable k−ε viscous model and energy equation were solved numerically using Ansys Fluent 2022R1. Examination of the residual and mesh independency were considered for checking the convergence of results. Optimal eddies' average kinetic energy per unit mass was formed near the t-junction not because of the earlier formed cold fronts but due to the recirculation of pressure at the 90o bend that affect the velocity of cold fluid substance from the two adjacent inlets (i.e. inlet 2 and inlet 3). Considering the variation of inlet velocity, three cases of cold front formation was examined. When the entry velocities of cold air/water and warm air/water are the same, the formation of the cold front is invisible at the early stage despite the fact that air flows faster than water. A significant difference exists between the heat transfer rate at hot and cold inlets, but the mass transfer is uniform at the three inlets. The optimal temperature across the motion of both fluids occurs at the circular surface 30mm after the mixture. The duct's bent nature is a factor that greatly influences the mixture of cold and warm liquid substances.